Pengaruh Sistem Informasi Pengadaan Barang terhadap Kepuasan Pelanggan di PT. Alpindo Mitra Baja Sukabumi - Qubaila Fazrin Ega Soraya; Indra Nanda (LP2M CBI PRESS, 2020)
The Problem that lifted in this research comprehension undercommunication about goods supplying information system concept that is used in company so that the happening of goods delivery slowness from warehouse to consumer. this research is done in customer PT. Alpindo Mitra Baja sukabumi, aim to detect to how goods supplying information system quality influence towards customer satisfaction at PT. Alpindo Mitra Baja sukabumi. problem that studied in this research how does goods supplying information system quality description, customer satisfaction description at PT. Alpindo Mitra Baja sukabumi, how big goods supplying information system influence towards customer satisfaction at PT. Alpindo Mitra Baja sukabumi. This research uses method survey explanation, the data collecting technique by inquiry distribution. instrument that used scale model inquiry likert. data analysis that used regression analysis. total consumers PT. Alpindo Mitra Baja sukabumi as much as 100 consumers so that the population size 100 person. data analysis is known that correlation coefficient between variable x (goods supplying information system) towards variable y (customer satisfaction) in tall category with value as big as 0.655. determination coefficient (kd) demoes that customer satisfaction is influenced by goods supplying information system as big as 42,9%. regression coefficient between variable x (goods supplying information system) and variable y (customer satisfaction) real existence. if mengonfirmasikan with hypothesis denial criteria demoes that ho aversed and h1 accepted. Research result conclusion demoes positive influential goods supplying information system towards customer satisfaction at PT. Alpindo Mitra Baja Sukabumi with value 16,799 + 0,660 (x). matter this means valuable customer satisfaction 16,799 otherwise there good goods supplying information system but if there good goods supplying information system so performance will increase as big as 0.660. marginally goods supplying information system conditon at PT. Alpindo Mitra Baja Sukabumi belong good category. Keywords : Influence, Information System, Procurement, Customer Satisfaction